When the type of assessment counteracts teaching for understanding. (3rd July 2018) - Leber, Jasmin; Renkl, Alexander; Nückles, Matthias; Wäschle, Kristin
ABSTRACT: According to the model of constructive alignment, learners adjust their learning strategies to the announced assessment (backwash effect). Hence, when teaching for understanding, the assessment method should be aligned with this teaching goal to ensure that learners engage in corresponding learning strategies. A quasi-experimental field study with 81 university students was conducted to test whether "downward misalignment" – such as using and announcing a fact-oriented test when trying to teach for understanding – reduces learners' use of sophisticated learning strategies, learning motivation, and learning outcomes in terms of understanding. We found that learners in the alignment condition applied more elaboration strategies and revealed better learning outcomes in terms of understanding. The well-aligned learning situation also led to higher perceived competence and less feeling of being under pressure. These findings confirm the backwash effect. For classroom practice, they underline the importance of carefully aligning teaching goals and assessment when teaching for understanding.